Resenhas - Heemann, Christiane; Claudia Pereira de Almeida, Ana; Endres Soares, Alícia; Brasil Irala, Valesca; Pereira Bittencourt, Guilherme (Revista Linguagem & Ensino, 2019)
Esta seção contém resenhas de cinco livros.